STRUCTURAL BIODIVERSITY OF TURKEY INTESTINES’ PARASITOCENOSES IN THE EASTERN REGION OF UKRAINE - Liulin, P. V.; Bogach, M. V. (Scientific Progress & Innovations, 2021)
Ecological and anthropogenic impacts together with changes in the forms of management, poultry concentrations lead to homeostatic disruption in the biotopes of parasitic systems, biodiversity of para-sitic coenoses of the intestine. The aim of the research was to find out the peculiarities of spreading, structural biodiversity of parasitic coenoses’ pathogens of turkeys’ intestines in the Eastern region of Ukraine. According to the results of research, the structural biodiversity of parasitic coenoses of tur-keys’ intestines on poultry farms of the Eastern region of Ukraine was determined. 15 species of path o-gens were identified, of which 8 species are representatives of protozoa: Apicomplexa, Zoomastyophora types and 7 species of helminthes: 5 species of nematode class, 2 species of cestode class. The effect of raising technologies and keeping systems of turkeys on the general infestation, biodiversity of parasito-cenoses, species indices (VIP, %) and correlations between the components of parasitocenoses have been established. According to the industrial technology of growing turkeys in cages, parasitocenosis was caused by 5 species of Eimeria spp. – VIP 100 %, the average EI made 28.78 %; when kept on a deep unchanged litter, the share of eimeriosis in the structure of parasitocenosis was VIP 87.8 %, asca-riasis – 10.04 %, heterakidosis – 2.15 % of the total infestation (EI 42.76 %). According to the tradi-tional extensive technology of growing turkeys using pastures and subsidiary farms, the total EI made 77.87 %, including mono-invasions – 48.2 %, two-, three-, four- and more component invasions, 25, 48 %; 3.64 %; 0.56 %, respectively. At turkeys’ intestines parasitocenoses occurrence,, a very high cor-relation was found between eimeriosis and trichomoniasis, between histomoniasis and ascariasis, heterakidosis, capillariasis and raietinosis, as well as between ascariasis and heterakidosis, capillaryo-sis and raietinosis (0.972–0.9,and very weak correlation between ascariasis, heterakidosis and raietino-sis (0.023–0.193). In addition, there was a weak negative correlation between histomoniasis and trich-omoniasis, trichomoniasis and ascariasis and heterakidosis (-0.132), indicating the presence of syner-gistic (high correlation) and competitive (weak and negative correlations) relationships between the components of intestinal parasitocenoses.